Clinical Cases in Exfoliative Dermatitis - Lotti, Torello M.; Wollina, Uwe.; Olisova, Olga.; Jafferany, Mohammad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Clinical cases are a key component in modern medical education, assisting the trainee or recertifying clinician to work through unusual cases using best practice techniques. Exfoliative dermatitis, also known as "red man", is an important discipline in this regard since it is a highly visual subject requiring the reader to describe often very subtle differences in the presentation of patients and define accurately the diagnostic and management criteria to base their clinical decision-making on. Clinical Cases in Exfoliative Dermatitis highlights evidence-based best practice through a multidisciplinary approach that is relevant to dermatologists, as well as pharmacologists and pathologists.
Drug eruption -- Dermatitis -- Atopic dermatitis -- Psoriasis -- Pityriasis rubra pilaris -- Contact dermatitis -- Stasis dermatitis (venous eczema) -- Seborrhoeic dermatitis -- Blistering diseases -- Sezary syndrome -- Congenital ichthyotic conditions -- Lymphoma and leukaemia -- Carcinoma of rectum, lung, fallopian tubes, colon, prostate -- Graft-versus-host disease -- HIV infection.
Keywords: Dermatology; Dermatology; Dermatitis